Utilization of intrauterine contraceptive device in a District of West Bengal, India - Haldar, A; Baur, B; Bhattacharya, SK; Das, R; Mundle, M; Saha, TK (Journal of Institute of Medicine Nepal, 2011)
Introduction: Lack of knowledge of contraceptive methods or source of supply, cost and poor access are the barriers that exist in developing countries and present study was conducted to assess the current intrauterine contraceptive device (IUCD) utilization by eligible couple in Howrah District of West Bengal.Methods: A community based cross sectional study using stratified multistage random sampling technique to obtain a sample size of 1600 using couple protection rate of West Bengal as 50%. So 12 villages and 4 urban wards were selected, with 125 sampled eligible couples in each village/ward to get 2000 eligible couples.Results: Contraceptive practice by any method was 63.3% and couple protection rate by modern method was 54.3%. IUCD use rate was 3%, oral contraceptive pill (OCP) use 25.4%, ligation 18.4%, condom 7.4%, and vasectomy 0.1%. Ever use rate of IUCD (Cu-T/Loop) was 6.3%, which increased significantly with advancement of maternal age, but was not associated with maternal literacy. Lack of motivation (43.4%), misconception (24.9%), unawareness (18.7%), unwillingness (10.9%) and religious/cultural barrier (4%) were the major reasons for underutilization of IUCD.Conclusions: IUCD acceptance is very low and different initiatives should be taken to improve it.